Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Power Point Dan Media Realia Terhadap Keterampilan Berpikir Kritis Siswa Pada Materi IPA Di Kelas V Sekolah Dasar - La Sisi; Chairan Zibar L. Parisu (Jurnal Sultra Elementary School, 2024)
The purpose of this study is to determine the improvement of students critical thingking skills in science learning which is taught using the PBL model assisted by powerpoint media and realia. This type of research is a quasi-experimental research (quasi-experimental). Based on the results of the study, there is an affect of critical thingking skills using PBL models assisted by powerpoint media and realia media, yhe everage N-Gain volue of students critical thingking skills in classes using BPL models assisted by powerpoint media is significantly higher that students using BPL model assisted by realia media, is based on the N-Gain average volue of the BPL model class  assisted by powerpoimt media, which is 0.58 higher that the BPL model class assisted by realia media, which is 0.48..